Studi literatur: Penggunaan Software Matematika Scratch terhadap Kemampuan Berpikir Komputasi Siswa tingkat Sekolah Dasar - Fitriani Fitriani; Yahfizham Yahfizham (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The aim of this study was to systematically find out the use of scratch arithmetic software against the computational thinking ability of elementary school students using literature study methods. Computational thinking is an important skill that students should develop from an early age to prepare them for the challenges of the 21st century. The method used in this study is a literature sales system to collect, analyze, and synthesize research findings on the use of scratch to improve computing thinking skills in elementary school students. Data sources come from Indonesian and English-language academic journals. Through exciting and fun visual programming activities, Scratch helps students improve their problem-solving skills, creativity, and collaborative skills. Scratch can also boost students’ interest in mathematics and computer science.